2015
DOI: 10.3109/03009742.2015.1016103
|View full text |Cite
|
Sign up to set email alerts
|

Serum leucine-rich α2-glycoprotein is a useful biomarker for monitoring disease activity in patients with adult-onset Still’s disease

Abstract: Serum LRG levels were increased in patients with AOSD and correlated well with disease activity measures. LRG may be a useful biomarker for distinguishing AOSD from RA and for monitoring the disease activity of AOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Recently, LRG1 has been recognized as a proinflammatory marker and found to be elevated in patients with ulcerative colitis, type 1 diabetes or RA ( 26 29 ). A previous study demonstrated that the serum levels of LRG1 were significantly higher in AOSD patients than in RA patients and HC subjects ( 30 ), which was consistent with our results that the urinary levels of LRG1 increased in patients with AOSD compared to those in non-AOSD subjects. Moreover, we demonstrated that the levels of LRG1 were positively correlated with the serum levels of the inflammatory cytokines IL-1β, IL-6, and IL-18 ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, LRG1 has been recognized as a proinflammatory marker and found to be elevated in patients with ulcerative colitis, type 1 diabetes or RA ( 26 29 ). A previous study demonstrated that the serum levels of LRG1 were significantly higher in AOSD patients than in RA patients and HC subjects ( 30 ), which was consistent with our results that the urinary levels of LRG1 increased in patients with AOSD compared to those in non-AOSD subjects. Moreover, we demonstrated that the levels of LRG1 were positively correlated with the serum levels of the inflammatory cytokines IL-1β, IL-6, and IL-18 ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…We originally identified LRG as an inflammatory biomarker for autoimmune diseases such as rheumatoid arthritis and inflammatory bowel disease (IBD) 9 . Subsequent studies from our group and others have shown that LRG is increased in various immune-related diseases such as adult-onset Still's disease 19 , psoriasis 20 , juvenile idiopathic arthritis 21 , Kawasaki disease 22 , appendicitis 23 and cancers 24,25 , indicating that LRG elevation is not limited to autoimmune diseases. In addition, LRG may serve as a biomarker for several other disease conditions such as heart failure 26 , diabetes-related complications [27][28][29] and obesity 30 , which are not typical inflammatory www.nature.com/scientificreports www.nature.com/scientificreports/ diseases but may involve immunopathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 89%
“…Increased LRG1 expression was also found in patients undergoing neurodegenerative diseases [ 23 ], acute appendicitis [ 9 ], hydrocephalus [ 24 ], heart failure [ 25 ], autoimmune diseases [ 12 ], and ageing [ 26 ]. LRG1 has also been suggested as promising biomarker in other disease entities, such as Still’s disease [ 27 ] and in peptidomics studies [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%